Reversible 4D-printing of shape memory polymers using heat and ethanol swelling - Lee, Amelia Yilin (Nanyang Technological University, 2020)
The advancements in smart materials have boosted additive manufacturing into a new form of printing known as 4D printing. 4D printing provides the means to create a dynamic structure for self-actuating devices fabricated by additive manufacturing techniques. Most existing 4D printing processes are only capable of one-way shape morphing using a single mechanism for stimulation. With increasing improvements in design and using multiple stimuli, reversible 4D printing has been proven to be feasible. This technology would eliminate the need for human interference, as the programming is driven by external stimuli, which allows 4D-printed parts to be actuated in multiple cycles. To combat the lack of reversibility in 4D-printing, this study introduces a new swelling, and the heat-driven reversible 4D-printing process developed to achieve contactless programming and recovery. The forward shape setting programming is realised by asymmetric swelling using ethanol and heating. The shape recovery is accomplished by drying and heating. The process was validated using a 4D-printed bilayer composite with a transition material (VeroWhitePlus) and an elastomer (TangoBlackPlus) that was printed with the PolyJet Connex500 printer. This et-swell (swelling by ethanol) and heat-driven process minimise the required materials to maintain the simplicity of the 4D-printed part. An analytical model has been developed to determine the shape after programming using different parameters to attain control over the shape morphing. The analytical model could be used to predict the curvatures with the given conditions. The values predicted by the analytical model was compared to the experimental results and yield an average error of 10.1%. The error of the model reduced to ~ 5% under conditions of low temperature, low transition material thickness and an elastomer thickness of 2 – 3 mm. To overcome these limits and to attain a better accuracy in the prediction of curvatures, a finite element analysis was conducted. It produced a lower error of ~ 4% in shape morphing accuracy and provided stress study to gain insight into the swell and heat-driven programming process. The study progressed to combine the stimuli to empower rapid response to the 4D-printing process. The entire shape morphing cycle could be completed within as short as 3 minutes. Twisting shape morphing motions were investigated to contribute more potential 3D-to-3D shape morphing during programming that are rarely achieved. The rapid response and twisting were incorporated into different designs such as flowers, butterfly and gripper to demonstrate potential applications for reversible 4D-printing of polymers in biomimetic and soft robotics.